Money and banking : an international text - Eyler, Robert (London ; New York : Routledge, 2010)
Focuses on the core issues in money and banking. This book provides students with a background in how financial markets work, how banks as businesses function, how central banks make decisions, and how monetary policy affects the global economy.
Includes bibliographical references and index.
oif 07/04/15
Loans
Keywords: Finance; Monetary policy; Banks and banking; International finance; Money and banking